Diplomasi Indonesia Dalam Meningkatkan Kunjungan Wisatawan dari Uni Emirat Arab Tahun 2016-2023 - Munawarah, Siti Fajriah; Saipuddin, Aisyah (Department of International Relations, Universitas Mulawarman, 2024)
Tourist visits from the Middle East to Indonesia continue to increase from year by year. Although tourists from Saudi Arabia still dominate the number of tourist visits from the Middle East, tourists from the United Arab Emirates (UAE) can not be underestimated. Based on the passenger exit survey of the Ministry of Tourism and Creative Economy of Indonesia, the state revenue from UAE tourist spending in 2015 reached 206 USD. Therefore, in 2016 the Indonesian government targets to increase the number of tourist arrivals from the UAE through multi-track diplomacy by the Indonesian government, non-governmental organizations, business people and individuals.